Violence in the public school of Manaus/AM: Impacts on the physical and mental health of teachers (Research, Society and Development, 2022)
The objective of this study is to investigate the violence suffered by teachers, their respective causal factors and existing conflict in the public school of Manaus AM. Methodology: The descriptive research, with a quantitative approach, carried out in the years 2020 and 2021, with a population of 70 individuals and a sample (N) 58 participants, teachers from the State Public School Professor Demóstenes Belduque Araújo Travessa, located in the Jorge Teixeira neighborhood, East Zone of Manaus. For data collection, a semi-structured electronic form containing open and closed questions was used. In order to determine the causal factors of violence. Results: The results indicate that the motivating factors of the student's aggressiveness against the teacher are: Broken families, reproduction of street behavior, presence of violence within the Family, troubled affective relationships, abusive use of alcohol and drugs. These aspects help to compose the profile of the aggressor student who is characterized by anger, intimidation and impulsiveness. In addition, the consequences of violence on the health and professional life of teachers are demonstrated in the forms of depression, low self-esteem, anxiety and fear, leading them to give up their teaching career or change schools. It was also noted the absence of strategies to combat violence and resolutions that involve the mediation of conflicts. In addition, there are no interdisciplinary projects aimed at promoting a culture of peace at school.